A critical study of electronic participation, transparency and open data in two Latin American countries. (25th August 2020) - Freitas, Jorge Lheureux De; Macadar, Marie Anne; Henriqson, Éder
This study compares two Latin American open government programs by focusing on electronic participation, transparency and open data practices in light of the theory of communicative action (TCA). The results show potential faults in the electronic participation and open data programs when substantial resources are not aligned with the governments' speeches and political wills. In addition, the investigation illustrates the value of adopting the TCA to investigate open programs from a critical perspective as a viable way to expand such research to other countries, portray the status quo of open government and improve policy making.